Examining the association between serum lactic dehydrogenase and all-cause mortality in patients with metabolic syndrome: a retrospective observational study. Issue 5 (23rd May 2016) - Wu, Li-Wei; Kao, Tung-Wei; Lin, Chien-Ming; Yang, Hui-Fang; Sun, Yu-Shan; Liaw, Fang-Yih; Wang, Chung-Ching; Peng, Tao-Chun; Chen, Wei-Liang
Abstract : Objectives: Emerging evidence indicates that elevated serum lactic dehydrogenase (LDH) levels are associated with increased cardiovascular mortality, but the mechanisms for this relationship remain uncertain. Since metabolic syndrome (MetS) is correlated with a higher risk of cardiovascular complications, we investigated the joint association between serum LDH levels and all-cause mortality in the US general population with MetS. Design: Retrospective study. Setting: The USA. Participants: A retrospective observational study of 3872 adults with MetS and 7516 adults without MetS in the National Health and Nutrition Examination Survey III was performed. Main outcome measures: Participants with and without MetS were both divided into 3 groups according to their serum LDH level. Multivariable Cox regression analyses and Kaplan-Meier survival probabilities were used to jointly relate all-cause, cardiovascular and cancer mortality risk to different serum LDH levels. Results: For all-cause mortality in participants with MetS, multivariable adjusted HRs were 1.006 (95% CI 0.837 to 1.210; p=0.947) for serum LDH of 149–176 U/L compared with 65–149 U/L, and 1.273 (95% CI 1.049 to 1.547; p=0.015) for serum LDH of 176–668 U/L compared with 65–149 U/L. Conclusions: Results support a positive association between higher level of serum LDH and mortality from all causes in individuals with MetS.